MANAJEMEN STRATEGIS DALAM MENINGKATKAN KEUNGGULAN KOMPETITIF DI SD MUHAMMADIYAH 1 BANDAR LAMPUNG - Putri, Yola Arjunita; Junaidah, Oki Dermawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In determining the success of an institution in achieving a competitive advantage, it could be seen based on the achievement of goals (performance and graduates), the increase in the number of students, a good reputation in the community (quality of educators and flagship programs), and the sustainability of the educational institution (vision and mission, and a strong organization through the role of the head of the madrasah). These indicators were observed at SD Muhammadiyah 1 Bandar Lampung; however, in this study, the researcher aimed to examine the sustainability of the school’s competitive advantage. Therefore, the objective of this research was to analyze and describe the strategic formulation, strategic implementation, and strategic evaluation in improving the competitive advantage of SD Muhammadiyah 1 Bandar Lampung.The research method used was qualitative, with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation at SD Muhammadiyah 1 Bandar Lampung related to strategic management in achieving a competitive advantage.The results of this study showed that the strategic formulation at SD Muhammadiyah 1 Bandar Lampung was conducted systematically and participatively by involving all stakeholders, in line with strategic management theory, which positions all school elements as the main actors in decision-making. The strategy implementation focused on innovative learning based on deep learning, the development of a dynamic curriculum including the Merdeka Curriculum, as well as a holistic marketing strategy that utilized social media and a reward system for teachers. Together, these efforts improved the quality of education, the school’s attractiveness, and the number of students. Strategic evaluation was conducted comprehensively and continuously with a focus on teacher performance, parent satisfaction, and alignment with the school’s vision and mission, thereby supporting adaptive decision-making and strengthening the school’s competitive position in facing educational dynamics.